The Effect of Tempeh Dietary Intake on Blood Glucose Levels in Prediabetics - Rotua, Manuntun; Sriwiyanti, Sriwiyanti (Chakra Brahmanda Lentera Institute, 2026)
Background: Rediabetes is a high-risk metabolic condition that precedes type 2 diabetes mellitus and is associated with increased morbidity. Dietary intervention plays a critical role in glycemic control. Tempeh, a traditional fermented soybean product, contains bioactive compounds such as isoflavones and high-quality protein that may improve glucose metabolism. However, evidence on its effectiveness in prediabetic populations remains limited. This study aimed to evaluate the effect of daily tempeh consumption on blood glucose levels among individuals with prediabetes. Methods: A comparative pre-experimental study with a pretest–posttest control group design was conducted at Mohammad Hoesin Hospital, Palembang. A total of 60 participants with prediabetes were randomly assigned to intervention (n=30) and control (n=30) groups. The intervention group received 250 g/day of tempeh for 14 days, while the control group followed a regular diet. Blood glucose levels were measured before and after the intervention. Data were analyzed using paired and independent t-tests with a significance level of p<0.05. Results: Baseline characteristics between groups were comparable (p>0.05). The intervention group showed a significant reduction in mean blood glucose levels from 139.83±16.52 mg/dL to 104.30±13.11 mg/dL (p<0.001), while the control group also showed a smaller decrease from 137.83±14.87 mg/dL to 121.93±13.09 mg/dL (p<0.001). The mean reduction was significantly greater in the intervention group (35.53 mg/dL) compared to the control group (15.90 mg/dL), with a statistically significant between-group difference (p<0.001). Conclusion: Daily consumption of 250 g tempeh for 14 days significantly reduces blood glucose levels in individuals with prediabetes. Tempeh may serve as an effective dietary strategy for glycemic control and prevention of diabetes progression.